2015
DOI: 10.1016/j.tiv.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Systematic in vitro toxicological screening of gold nanoparticles designed for nanomedicine applications

Abstract: Gold nanoparticles (AuNP) are increasingly being applied in the biomedical field as therapeutics, contrast agents, and in diagnostic systems, motivating investigations of their toxicity that might arise from accidental exposure. While other work has investigated the toxicological response to gold nanoparticles for industrial purposes, here we have surveyed formulations that have been developed for biomedical use, are in clinical trials or have been FDA-approved. The AuNP library tested contains a range of shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 49 publications
2
62
0
Order By: Relevance
“…the bone marrow, the liver, and the spleen, confirmed by the TEM of these tissues, which revealed retention in the macrophages. These findings supported the results of Naha et al 12 that typically observed macrophages to be more sensitive to AuNP as compared to epithelial and fibroblast cells, likely due to their higher phagocytic activity and thus higher uptake of nanoparticles. Thus we corroborated the results of Cai et al 9 who demonstrated that AuNP are taken up by the MPS organs.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…the bone marrow, the liver, and the spleen, confirmed by the TEM of these tissues, which revealed retention in the macrophages. These findings supported the results of Naha et al 12 that typically observed macrophages to be more sensitive to AuNP as compared to epithelial and fibroblast cells, likely due to their higher phagocytic activity and thus higher uptake of nanoparticles. Thus we corroborated the results of Cai et al 9 who demonstrated that AuNP are taken up by the MPS organs.…”
Section: Resultssupporting
confidence: 91%
“…Previously, Naha et al . 12 have shown good cytocompatibility in vitro for this AuNP, with no effect on cell cytoskeleton or cell spreading.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Graphite flakes, chloroacetic acid, sodium hydroxide, poly(ethyleneglycol)-bis(3-aminopropyl) (NH2PEGNH2, Mw = 1.5 kDa), N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide (98%, EDC), cetyltrimethylammonium bromide (CTAB), tetrachloroauric acid trihydrate (HAuCl4·3H2O), silver nitrate (AgNO3), ascorbic acid, sodium borohydride (NaBH4), paraformaldehyde, hydrochloric acid, fluorescein-isothiocyanate (FITC), Fluoroshield™ with 1,4-DOI: 10 …”
Section: Experimental Section Materialsmentioning
confidence: 99%